Hydrogeological investigations of Chapai Nawabganj town of Nawabganj district, North-West Bangladesh using isotope and other techniques (Journal of Bangladesh Academy of Sciences, 2014)
Groundwater of Chapai Nawabganj town has been studied using hydrogeological, hydrochemical and environmental isotope (?18O, ?2H, ?13C, 3H and 14C) data. Aquifer underneath the study area is divided into unconfined to semi-confined Holocene alluvial floodplain aquifer and confined Plio-Pleistocene Dupi Tila sandstone aquifer. Chemical composition of groundwater is characterized by high concentrations of Mg2+, Na+, Ca2+, HCO3-, FeTotal, and low concentrations of Mn2+, NO3 - and PO4 3-. Groundwater samples are mainly Mg-Ca-HCO3 and Na-Mg-Ca-HCO3 types and Na-Mg-Ca-Cl-HCO3 type of water is also found at some places. Based on Cl- and SO42- concentrations groundwater is normal chloride and normal sulphate water, respectively. In terms of SAR and EC values water is excellent for irrigation purpose. The isotopic composition also suggests some segregation of groundwater from the different aquifers and indicates different ages of recharge. DOI: http://dx.doi.org/10.3329/jbas.v38i2.21338 Journal of Bangladesh Academy of Sciences, Vol. 38, No. 2, 131-142, 2014